Analisis Pengaruh Perceived Meaningful Work, Environmental Transformational Leadership Terhadap Organizational Citizenship Behavior Towards the Environment di Hotel Mercure dan Ibis Samarinda [Effect of Perceived Meaningful Work, Environmental Transformational Leadership on Organizational Citizenship Behavior Towards the Environment at Mercure Hotel and Ibis Samarinda] - Laurie, Shania; Hutabarat, Zoel (Feedforward: Journal of Human Resource, 2022)
An entrepreneur needs to maintain the sustainability of Natural Resources. The aim of this study is to determine the effect of perceived meaningful work and environment transformational leadership on organizational citizenship behavior towards the environment. This research is quantitative research with non-probability sampling method by distributing questionnaires to respondents who are all employees of Mercure and Ibis Samarinda hotels. For the pretest, the respondent's data was collected 30 respondents, while for the sample in the actual test, 222 respondents were collected. The collected data was then processed using the Partial Least Square Structural Equation Model (PLS-SEM) and analyzed further with validity, reliability, bias, and hypotheses testing. The results of the research conducted indicate that the ETL variable has a direct effect on OCBE and also has an indirect effect on OCBE, the PMW variable as a mediating variable. Likewise, the direct effect of ETL on PWM and the direct influence of PMW on OCBE.BAHASA INDONESIA ABSTRACTPelaku bisnis perlu menjaga keberlanjutan Sumber Daya Alam (SDA). Penelitian ini ingin mengetahui pengaruh perceived meaningful work (PMW) dan environment transformational leadership (ETL) terhadap Organizational Citizenship Behavior towards the Environment (OCBE). Penelitian ini merupakan penelitian kuantitatif dengan metode non-probability sampling dengan menyebarkan kuesioner kepada responden yang adalah seluruh karyawan hotel Mercure dan Ibis Samarinda. Untuk pretest, terkumpul data responden sebanyak 30 responden, sedangkan untuk sampel pada actual test terkumpul 222 responden. Data yang terkumpul kemudian diolah dengan menggunakan alat uji Partial Least Square Structural Equation Model (PLS-SEM) dan dianalisis lebih lanjut dengan validitas, reliabilitas, bias, dan hipotesis yang telah dibentuk. Hasil penelitian yang dilakukan menunjukkan bahwa variabel ETL memiliki pengaruh langsung terhadap OCBE dan juga berpengaruh tidak langsung terhadap OCBE variabel PMW sebagai variabel mediasi. Demikian juga dengan pengaruh langsung ETL terhadap PWM dan pengaruh langsung PMW terhadap OCBE.